2017
DOI: 10.1161/circep.116.004998
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Intramyocardial Adipose Tissue on the Accuracy of Endocardial Contact Mapping of the Chronic Myocardial Infarction Substrate

Abstract: These novel findings enhance our understanding of the confounding influence of IMAT on endocardial scar mapping. Combined bipolar and unipolar voltage mapping using optimal thresholds may be useful for delineating IMAT dense regions of myocardium, in postinfarct cardiomyopathy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 36 publications
0
8
0
Order By: Relevance
“…No consensus has been reached about the potential endocrinological role of intramyocardial fat in heart disease nor its relation to conductive system disturbances, especially with sudden cardiac death [42, 5153]. Recent studies have demonstrated that intramyocardial fat contributes to ventricular electrophysiological remodelling in patients with ischemic heart disease and influences endocardial scar mapping during electrophysiological exams of ventricular tachycardia [54, 55].…”
Section: Cardiac Visceral Adipose Tissuementioning
confidence: 99%
“…No consensus has been reached about the potential endocrinological role of intramyocardial fat in heart disease nor its relation to conductive system disturbances, especially with sudden cardiac death [42, 5153]. Recent studies have demonstrated that intramyocardial fat contributes to ventricular electrophysiological remodelling in patients with ischemic heart disease and influences endocardial scar mapping during electrophysiological exams of ventricular tachycardia [54, 55].…”
Section: Cardiac Visceral Adipose Tissuementioning
confidence: 99%
“…Cardiac fat has been shown to carry important diagnostic information to characterize lipomatous metaplasia, 15 which has high prevalence and prognostic value in patients with myocardial infarction. 16,17 Moreover, water and fat partial volume is a known source of error in parametric mapping, 18 and previous works have explored simultaneous T 1 and fat imaging to reduce partial volume effects and quantify epicardial fat volumes. 19 Therefore, the extension of cardiac MRF to enable additional fat fraction (FF) quantification and partial volume correction is desired.…”
Section: Introductionmentioning
confidence: 99%
“…Fat quantification is a useful biomarker to characterize infarction and fatty infiltration [55]; additionally, fatty infiltrations can introduce bias in myocardial tissue characterization [56]. Cardiac MRF has been extended to simultaneous T 1 , T 2 , and fat fraction quantification [57] at 1.5T.…”
Section: Introductionmentioning
confidence: 99%